Implementation of MCDM Approaches for a Real-Life Location Selection Problem: A Case Study of Consumer Goods Sector - EMİR, OĞUZ (Springer-Verlag Singapore Pte Ltd., 2022)
Selecting a suitable warehouse location elevates the supply chain performance by reducing the lead times and increasing the response efficiency. Hence, location selection emerges as a strategic decision-making problem for competitive advantage. In this paper, a real decision-making problem of a multinational company operating in the consumer goods sector has been examined. The company's Turkey office is responsible for the operations in many regions such as Middle East, Africa, Central Asia, and Eastern Europe. A case study is handled by the logistics network planning team of the company to evaluate the new warehouse request coming from the regional sales team. For this decision problem, two different multi-criteria decision-making methods TOPSIS and VIKOR, are employed to evaluate four alternative scenarios. In addition, the AHP technique is also applied to determine criteria weights. The results of both methods revealed the same alternative as the best decision.
21st International Symposium on Production Research (ISPR) - Digitizing Production System
▪ Book Series: Lecture Notes in Mechanical Engineering.
Keywords: Multi Criteria Decision Making; Analytical Hierarchy Process; TOPSIS; VIKOR